Variation in Straw Grain Ratio and Straw Quality in Different Rice Cultivars of India - Das, Madan Mohan; Misra, Asim Kumar; Singh, Krishna Kunwar; Pailan, Gaur Hari; Khan, Tanveer Ahmed (Indian Journal of Animal Nutrition, 2019)
Straw grain ratio (S/G ratio) of paddy cultivars available across the country in different states was determined. Variation in straw quality was also estimated. Sampling locations were basically from farmers field spread over 9 major paddy producing states viz., Bihar, Chhatishgarh, Gujrat, Haryana, Jharkhand, Tamilnadu, Uttar Pradesh, Uttrakhand and West Bengal. A significant variation (P